2011
DOI: 10.4103/0971-4065.83727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extract of Tribulus terrestris on oxalate-induced oxidative stress in rats

Abstract: The present study was aimed at studying the effect of Tribulus terrestris on different parameters of oxidative stress and gene expression profiles of antioxidant enzymes in renal tissues of male wistar rats after induction of hyperoxaluria. The animals were divided into three groups. The animals in group I (control) were administered vehicle only. In group II, the animals were treated with ethylene glycol (hyperoxaluric agent) and those in group III were administered T. terrestris plant extract in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…In addition, the reported anti-oxidant activity of METT in this study was evident from the enhancement of activities of testicular anti-oxidant enzymes. The anti-oxidant effect of T. terrestris extract was similar to that previously demonstrated [ 32 , 33 ]. The anti-oxidant activity of T. terrestris fruits was attributed to the presence of active derivatives of 4,5-di-p-coumaroylquinic acid, which were isolated from the fruits and reported to have potent anti-oxidant activity [ 34 ].…”
Section: Disscusionsupporting
confidence: 89%
“…In addition, the reported anti-oxidant activity of METT in this study was evident from the enhancement of activities of testicular anti-oxidant enzymes. The anti-oxidant effect of T. terrestris extract was similar to that previously demonstrated [ 32 , 33 ]. The anti-oxidant activity of T. terrestris fruits was attributed to the presence of active derivatives of 4,5-di-p-coumaroylquinic acid, which were isolated from the fruits and reported to have potent anti-oxidant activity [ 34 ].…”
Section: Disscusionsupporting
confidence: 89%
“…Tribulus terrestris were shown to increase the nitric oxide release and this is considered for its aphrodisiac capacity character [48, 49]. Our results suggested major increases in Nrf-2 and HO-1 levels and decreases in NF-κB and MDA levels of the various reproductive tissue parts and serum when administered with Tribulus terrestris similarly to a study which the extract was restored antioxidant enzyme activity and their expression profile in kidney tissue [50] and another study that extract blocked proliferation and induced apoptosis in cancer cells through the inhibition of NF-κB signaling [51]. …”
Section: Discussionsupporting
confidence: 72%
“…Its target organ is the liver, and it is effective for the control of headaches, dizziness, breast lumps, chest pain, flank pain, intestinal pain, and problems with breast milk circulation. Modern pharmacological studies have detailed its various effects against diabetes [ 8 ] and liver and kidney toxicity [ 7 ] as well as oxidative damage [ 10 ], but its herbal features and clinical efficacy are not well known. Therefore, in this study, we investigated the efficacy of TF extract with or without 0.1% HC to improve AD using an Ox-induced AD mice compared to 1% HC application as a common topical dosage.…”
Section: Discussionmentioning
confidence: 99%
“…TF is also used in folk medicine for a tonic, aphrodisiac, palliative, astringent, stomachic, antihypertensive, diuretic, lithontriptic, and urinary anti-infective agents [ 5 ]. In modern experimental studies, TF has been reported to have protective effects against liver and kidney toxicity [ 6 – 9 ], antidiabetic effects [ 8 ], and antioxidant effects [ 10 ]. This plant contains known bioactive compounds, such as cytoprotective lignanamides [ 10 ], anthelminthic [ 11 ] and antifungal saponin [ 12 ], and anti-inflammatory N-trans- ρ -caffeoyl tyramine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%